Morfometrik, Meristik dan Pola Pertumbuhan Ikan Katung (Pristolepis grootii Bleeker) Di Danau Pekak Desa Buluh Nipis Kecamatan Siak Hulu Kabupaten Kampar Provinsi Riau - Siburian, Sades; Putra, Ridwan Manda; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Pristolepis grootii is a type of freshwater fish that commonly inhabit the Pekak Lake, but information on biological aspects of this fish, including morphometric, meristic, and growth patterns is rare. To understand those characteristics, a research had been conducted from November 2017 to January 2018. There were 100 fishes (54-125 mm SL and 7.87-89.04 gr BW) were captured from the lake. There were 26 morphological characteristics measured and 10 meristical characteristics counted. Results hown that the meristical characteristics were as follows: D.XII-XIV.13-16, P.26, V.II-VIII.8-10, A.III.6-8, C.12-14, the number of scales in the pre-dorsal fin was 10-12, around the body was 18-32, in the caudal peduncle was 6-14, and in the lateral line was 38-48. The only morphometrical characteristic that shown difference in male and female was the distance between mouth and eye, it was shorter in male. The length-weight relationship shown that the growth pattern in male and female was similar, it was negative allometric (b= 2.57). The water quality parameters shown that temperature 30.5°C, transparency 76.25 cm, pH 6, DO 6.44 mg/L, CO29.74 mg/L and depth 5 m, Nitrate 0.2521 mg/L and Phosphate 0.1504 mg/L. Key words: freshwater fish, oxbow lake, negative allometric, length-weight